Kajian Kebijakan Strategi Pelaksanaan Program Eliminasi Malaria di Kabupaten Halmahera Selatan - Sumiati Tomia; Kartini M Ali; Rony Puasa; Husen Alhadar (Jurnal Sehat Mandiri, 2024)
Eliminating malaria through reviewing government policies and implementing effective prevention programs has become a major focus in efforts to reduce the burden of this disease. The aim of this research is to examine the implementation of Minister of Health Decree No. 293 of 2009 concerning malaria elimination policies including understanding, implementation, commitment, innovation and sustainability. This research design uses a qualitative design with a descriptive research type using an interview method using a questionnaire. Researchers conducted theme analysis using qualitative data. This research was conducted at 7 Community Health Centers in South Halmahera Regency. The population in this study were people who worked in community health centers, with the sample being the head of the community health center, malaria program manager and laboratory staff. Research shows 85.8% of malaria elimination requirements in South Halmahera Regency, with several requirements that do not comply with assessment standards, and positive cases of malaria reported by community health centers. In conclusion, to achieve malaria elimination status in districts/cities, three conditions must be met: API rate <1 per thousand population, positivity rate <5%, and no local transmission in the last 3 years. Advice to policy holders is to carry out regular monitoring and evaluation of activities to increase community participation, improve communication and maintain control programs.